Is the Westminster System Broken Beyond Repair?. Issue 4 (5th August 2016) - Grube, Dennis C.; Howard, Cosmo
Abstract : Is Westminster dying as a useful conceptual encapsulation of a particular system of public administration? Scholarly critiques over the last decade have suggested Westminster civil services are evolving in ways that erode crucial Westminster "traditions." Core elements including security of tenure, merit‐based selection, non‐partisanship, anonymity, and ministerial responsibility are all perceived as in decline or under attack. Influential commentators have proposed concepts such as "new political governance, " changing "public sector bargains, " "court government/politics, " and "presidentialization" to document and interpret these allegedly paradigmatic shifts in public administration. This article places these in context by canvasing different accounts of what Westminster is, before assessing the critiques about what it has become. The article argues that Westminster is not broken beyond repair, but rather it has been remolded to suit the needs of contemporary governance.